The economic impact of cultural event towards host community in Kota Bharu, Kelantan - Nor Shahida Said; Siti Murni Rashid; Yee Han Wei (2016)
The cultural events have not only a key cultural and social value, but also an interesting economic impact. The cultural sectors nowadays represent a productive economic sector, which is growing in importance. At the same time, economic impact analysis is a frequently discussed topic in academic papers and journals to assess the relevance of the culture in the local economies. In many cases the positive economic effects described in these publications are used to justify a further development of tourism and cultural events. The main aim of this research is to highlight the economic impacts on cultural events. The impacts are calculated on increased tourist visit, job creation and business opportunities. There are a total number 384 of respondents from Kota Bharu, Kelantan are contributed in this study. In order to measure the relationship between economic impacts on cultural events towards host communities in Kota Bharu, Kelantan, the correlation analysis will be used. In the meantime, the data of this study will be collected through the distribution of questionnaire to respondents and will be processed by using Statistical Package for Social Sciences (SPSS).